MONITORING IMPLEMENTASI PENDEKATAN PRAGMATIKA DINAMIS PEMBELAJARAN GURU AGAMA HINDU - I Gusti Made Suratmaja (Pascasarjana Universitas Hindu Indonesia, 2015)
The application of the dynamic pragmatic learning within the Hinduism subject has brought about positive impact on the increase of the student learning motivation. It is indicated through the number of students that gave statement if they felt interested and stimulated by the application of such method within the subject in which hence the learning motivation was increasing. The academic supervision conducted by the school superintendents has implicated positively as well towards the increase of the teacher competence, in particular in understanding and implementing the innovative model, approach, and strategy of learning.